Investigation of DDT resistance mechanisms in Anopheles funestus populations from northern and southern Benin reveals a key role of the GSTe2 gene. - Tchigossou, Genevieve M; Atoyebi, Seun M; Akoton, Romaric; TOSSOU, Eric; DJEGBE, Innocent; Riveron, Jacob; Irving, Helen; YESSOUFOU, AKADIRI (My University, 2020)
Abstract Background: Understanding the molecular basis of insecticide resistance in mosquito, such as Anopheles funestus, is an important step in developing strategies to mitigate the resistance problem. This study aims to assess the role of the GSTe2 gene in DDT resistance and determine the genetic diversity of this gene in An. funestus. Methods: Gene expression analysis was performed using microarrays and PCR while the potential mutation associated with resistance was determined using sequencing. Results: Low expression level of GSTe2 gene was recorded in Burkina-Faso samples with a fold change of 3.3 while high expression (FC 35.6) was recorded in southern Benin in Pahou (FC 35.6) and Kpome (FC 13.3). The sequencing of GSTe2 gene in six localities showed that L119F-GSTe2 mutation is almost getting fixed in highly DDT-resistant Benin (Pahou, Kpome, Doukonta) and Nigeria (Akaka Remo) mosquitoes with a low mutation rate observed in Tanongou (Benin) and Burkina-Faso mosquitoes. Conclusion: This study shows the key role of the GSTe2 gene in DDT resistant An. funestus in Benin. Polymorphism analysis of this gene across Benin revealed possible barriers to gene flow, which could impact the design and implementation of resistance management strategies in the country
Keywords: Anopheles funestus; Benin; DDT; GSTe2; Mechanism of resistance